A comparison of accuracy and stroke characteristics between two putting grip techniques - Park, Y.; O'Sullivan, D.; Shin, I.; Chung, C.; Lee, G.; Shin, H. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Nowadays PGA golfers are experimenting with various golf putting grips. The purpose of this study was to investigate the traits of using two putting grips; reverse overlapping grip and finger bone grip at three different putting distances. 20 subjects with no previous golf experience participated in this study. The kinematic data of the subject and the putter`s shaft and head was recorded by 8 Qualisys cameras at 100Hz. There was no significant difference between the success rate of getting the ball in the hole at all distances. The finger bone grip produced statistically smaller radial error values than the reverse overlapping grip at the distances for 7 and 11 metres. The finger bone grip provided straighter putter head trajectories and less change in the movement of the COG, which implies more stability of the player and that the ball will travel in the desired path. In conclusion, the finger bone putting technique gave radial errors less than the reverse overlapping grip technique which seems to be due to the added stability and straighter putter head trajectories.